Report on the construction of portable NIRS equation to estimate forage quality in Brachiaria decumbens-ruzisiensis-brizantha species complex - Castiblanco, Valheria; Mazabel, Johanna (Bioversity International and the International Center for Tropical Agriculture, 2021)
The nutritive value of Brachiaria Hybrids is one of the most important parameters in the forages breeding program at the International Center for Tropical Agriculture (CIAT). It supports the selection and identification of promising genotypes. Using Near infrared reflectance spectroscopy (NIRS) we have been able to estimate protein contents (CP), neutral detergent fiber (NDF), and acid detergent fiber (ADF) with satisfactory results in the benchtop NIRS of the sample dried and ground. During 2021, the portable NIRS has been explored for the prediction of nutritional quality parameters without the destructive preprocessing of plants. This allows a rapid assessment of nutritive values. The objectives of this study were to evaluate the potential use of portable NIRS technology into the breeding program to predict the nutritional quality of interspecific Brachiaria Hybrids and extend the data set of calibration for building models for measure dry matter (DM), NDF, ADF and CP. The methodology applied used wavelengths of full range (350-2500nm) and NIR (1000-2500nm). Prediction accuracy of the obtained equations were in general better than previous models, but unfortunately still not robust enough to be applied. Further enrichment of the calibration set is required.